Mega-project engineering-management processes: pre-planning phase evaluation for construction and mining - Albishri, Abdulaziz Ali M (Curtin University, 2015)
Mega-projects internationally continue to experience time and cost overruns. Addressing the pre-planning phase has been assessed as a key requirement. This research-project presents two KSA mega-project resources case-studies towards an evaluation of the management-processes applied at the preplanning, design, construction and design phases to clarify procedure and recommend improvement. Findings note the impact of Stage-Gate Process, Gate-keeper approval, and scope-change processes. Recommendations for a best practice stakeholder guide are developed towards best practice.